Anatomical and Functional Outcome of Suprachoroidal Triamcinolone Injection in Patients of Refractive Diabetic Macular Oedema - Arshad, Madiha; Arshad, Wajeeha; Mazhar, Syed Abdullah; Arshad, Samia; Arshad, Sohaib (Biological and Clinical Sciences Research Journal, 2025)
The most frequent cause of central vision loss in people with diabetes with diabetic retinopathy is diabetic macular edema (DME). Recently, there has been a greater interest in investigating the suprachoroidal space for medication administration to lessen the adverse effects of intravitreal steroids. Objective: "To determine mean change in macular thickness and best corrected visual acuity after suprachoroidal triamcinolone injection in patients of refractive diabetic macular oedema. Quasi-experimental study. Department of Ophthalmology, DHQ Hospital, Sahiwal, from 07-12-2021 to 07-06-2022. Methodology: Sixty eyes fulfilling selection criteria were enrolled and received an injection of triamcinolone acetonide. All patients were dilated before injection, and an indirect ophthalmoscope was placed in their hands to examine the fundus after injection. At baseline and after one month, the central macular thickened, BCVA was measured, and the change was calculated. Results: The mean age was calculated as 59.06 ± 6.02 years. Duration of diabetes was 5.36 ± 1.94 years and duration of symptoms 18.15 ± 6.57 days. Baseline BCVA was 0.28 ± 0.02, and post-treatment BCVA was 0.67 ± 0.11. Baseline central macular thickness was 469.31 ± 24.12, and post-treatment central macular thickness was 292.48 ± 8.38. The distribution of change in BCVA was 0.39 ± 0.09, and central macular thickness was 176.83 ± 15.74 (p=0.000). Our study had 75.0 %( n=45) males and 25.0% (n=15) females. Distribution of lateral side was done, 66.7 %( n=40) had left side affected and 33.3 %( n=20) had right side. Conclusion: Thus, suprachoroidal triamcinolone injection may help improve macular thickness and BCVA in patients with refractive diabetic macular oedema.